Keutamaan Air Wudu sebagai Kecantikan Wajah: Studi Takhrij dan Syarah Hadis - Najla, Zhafirah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith regarding the virtues of ablution water as facial beauty through the application of takhrij and syarah hadith studies. This research method uses a qualitative approach through literature study related to contemporary analysis. The results of this study found that the hadith about the virtue of ablution as facial beauty is authentic in terms of sanad and matan. The discussion of this research is that on the Day of Resurrection, the people of the Prophet Muhammad. will be presented with a radiant face because of the remnants of the ablution water. The conclusion of this study is that cleanliness, chastity, and beauty can be maintained by carrying out ablution seriously without having to bother looking for and buying the right beauty products for the face. This research is expected to provide special benefits for women in the contemporary era.